Pulmonary schistosomiasis: bronchopneumonitis probably due to schistosomulae - Ênio Roberto Pietra Pedroso; José Roberto Lambertucci; Manoel Otávio da Costa Rocha; Dirceu Bartolomeu Greco; Cid Sérgio Ferreira; Davidson Pires de Lima; Pedro Raso (Revista da Sociedade Brasileira de Medicina Tropical, 1984)
A clinical and radiological picture of bronchopneumonia was observed in a patient between the second and third weeks post-infection with cercariae of S. mansoni. There was a spontaneous recovery without sequelae in 20 days and the clinical and radiological alterations were interpreted as associated with the passage of schistosomulae through the lungs.